Literature Review on Microstructure and Mechanical Properties of Ss400 Steel Due To Variations in PWHT Temperature in the GMAW Welding Process - Aprianto, Edo; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
Post-Weld Heat Treatment (PWHT) is a widely employed thermal method used to relieve residual stresses and enhance the mechanical properties of welded joints. This study investigates the effect of PWHT on the mechanical and microstructural properties of SS400 steel welded using the Gas Metal Arc Welding (GMAW) process. The research focuses on evaluating how variations in PWHT temperature influence tensile strength. impact toughness. hardness. and microstructural characteristics. Specimens were subjected to PWHT for 1 hour with a 15-minute holding time. followed by natural cooling at room temperature. The results indicate that PWHT significantly improves impact toughness and refines grain structure. especially in the Heat Affected Zone (HAZ). while leading to a reduction in tensile strength compared to untreated specimens. Higher PWHT temperatures promoted the formation of finer ferrite and bainitic phases. contributing to enhanced ductility and toughness but reduced hardness due to grain coarsening. Microstructural analysis confirmed a shift in phase composition. where an increased ferrite content resulted in lower hardness. while a dominant pearlite phase corresponded with higher hardness values. Overall. this study highlights the importance of optimizing PWHT parameters to achieve a desirable balance between strength. hardness. and toughness in SS400 welded joints. particularly for structural applications such as shipbuilding.